How Intangible Cultural Heritage can be Safeguarded in Kampung Tourism by Local Community? - Suryani, Adi; Prasetyawati, Niken; Suarmini, Ni Wayan; Saifulloh, Moh.; Muhibbin, Zainul; Soedarso, Soedarso; Rizkiantono, Raditya Eka (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
Local heritage culture is an invaluable asset. It is not just establishing an identity that distinguishes one community apart from another. The local culture has recently been recognized as a resource that can help improve the quality of life in the community. Tourism is one of the many ways to improve the quality of life for the local population while preserving the local culture. The goal of this research is to investigate how a local community uses local tourism to preserve their culture. The study is carried out in Among Budoyo, Desa Wage. One local community member who actively manages the tourist destination serves as the key informant. The study uses a qualitative approach. Direct observation and semi-structured interviews are used to collect the data. The study concludes that by enhancing the roles of human resources in fostering tourism, the local community maintains both their local culture and tourism. There are two primary methods used by local community of Desa Wage. The first is by expanding the roles and capabilities of community-based organizations to promote tourism and community development. Community-based organizations serve as a venue or channel for the local community to come together, engage, and share ideas that are beneficial. They also help to create working groups, network, collaborate with outside organizations, and start the process of empowerment. Developing the internal strength of the community is the second method. Positive attitudes, like strong commitment, initiative, perseverance, independence, and motivation, are often fostered in the local community of Desa Wage.